Pola Komunikasi dalam Penanaman Nilai-Nilai Keagaman Anak Usia Dini di Sekolah TPQ Ash-Shodiqin Bantar Kemangan Bogor Timur Kota - nurmah, siti; Kamalludin; Putri Ria Angelina (Komunika: Journal of Communication Science and Islamic Dakwah, 2025)
Verbal communication is determined as speak or oral or writing which are manifestations of language as a medium of message exchange. Early children in the growth and development of physical (fine and gross motoric coordination), intelligence (mind, creative, emotional intelligence, spiritual intelligence), socio-emotional (attitude and behavior and religion), language and communication, and with uniqueness and stages -stage of development through by early children. This research uses a qualitative approach, related to social facts in the community, data collection techniques through interview and observation and documentation. The results of the learning while playing method are the same, teachers deliver the material with accompanyed games such as singing, applauding, or in other games. Messages delivered are also verbal and nonverbal and will get immediate response or feedback, so the teacher will immediately receive response. The using method is also like that, the teacher delivers verbal and nonverbal messages, with language and signs, the difference of these signs are in the form of examples or examples by the teacher and student responses get immediately.